125k views
1 vote
when solving this, do i take it out of the parenthesis or make it into a square root? because its very confusing.

when solving this, do i take it out of the parenthesis or make it into a square root-example-1
User Pjz
by
6.0k points

1 Answer

5 votes

Finding the inverse function:

We are given a function y = f(x). To find the inverse function, we exchange x with y in the original function, and then isolate y.

So

We are given the function:


f(x)=(x+7)^5

So


y=(x+7)^5

Changing x with y


x=(y+7_{})^5

Now, we have to isolate y. So


(y+7)^5=x

We can apply the fifth root to both sides. So:


\sqrt[5]{(y+7)^5}=\sqrt[5]{x}
y+7=\sqrt[5]{x}
f^(-1)(x)=y=\sqrt[5]{x}-7

User MickeyThreeSheds
by
6.0k points